Design of Personal Trajectories for Employees’ Professional Development in the Knowledge Society under Industry 5.0 - Ekaterina V. Orlova (MDPI AG, 2021)
The main feature of Industry 5.0 is “personalization”, linked not only to provide customers with personalized products, but also, in our opinion, to ensure personalization in labor relations with employees, since it increases human value through human–machine collaboration. The human capital quality determines a significant contribution not only to the labor productivity growth, but also to extend a social communication, loyalty and employees’ trust. The study proposes the new methodological approach for corporate human capital assessment and management (CHCM) over new conditions of digital transformation. The CHCM uses methods of system analysis and synthesis, expert assessments, descriptive statistical analysis and survey. The novelty of CHCM is that, firstly, it reflects all the essential features and properties of human capital under emergence of new professions; secondly, it combines and comprehensively uses both quantitative and qualitative methods for human capital assessment, reflecting the subjective and objective aspects of human capital measurement; thirdly, it allows to create warranted management decisions about individual trajectories of professional development of employees, ensuring the continuous growth of individual, corporate and social wealth. It is proved experimentally that the implementation of individual trajectories for employees’ professional development provides 2–3 years’ perspective on companies’ performance growth.